Single-cell transcriptomic characterization reveals the landscape of airway remodeling and inflammation in a cynomolgus monkey model of asthma - Wang, Yingshuo; Dong, Xinyan; Pan, Caizhe; Zhu, Cihang; Qi, Hantao; Wang, Yifan; Wei, Hao; Xie, Qiangmin; Wu, Lei; Shen, Huijuan; Li, Shuxian; Xie, Yicheng (Frontiers in Immunology, 2022)
Monkey disease models, which are comparable to humans in terms of genetic, anatomical, and physiological characteristics, are important for understanding disease mechanisms and evaluating the efficiency of biological treatments. Here, we established an A.suum-induced model of asthma in cynomolgus monkeys to profile airway inflammation and remodeling in the lungs by single-cell RNA sequencing (scRNA-seq). The asthma model results in airway hyperresponsiveness and remodeling, demonstrated by pulmonary function test and histological characterization. scRNA-seq reveals that the model elevates the numbers of stromal, epithelial and mesenchymal cells (MCs). Particularly, the model increases the numbers of endothelial cells (ECs), fibroblasts (Fibs) and smooth muscle cells (SMCs) in the lungs, with upregulated gene expression associated with cell functions enriched in cell migration and angiogenesis in ECs and Fibs, and VEGF-driven cell proliferation, apoptotic process and complement activation in SMCs. Interestingly, we discover a novel Fib subtype that mediates type I inflammation in the asthmatic lungs. Moreover, MCs in the asthmatic lungs are found to regulate airway remodeling and immunological responses, with elevated gene expression enriched in cell migration, proliferation, angiogenesis and innate immunological responses. Not only the numbers of epithelial cells in the asthmatic lungs change at the time of lung tissue collection, but also their gene expressions are significantly altered, with an enrichment in the biological processes of IL-17 signaling pathway and apoptosis in the majority of subtypes of epithelial cells. Moreover, the ubiquitin process and DNA repair are more prevalent in ciliated epithelial cells. Last, cell-to-cell interaction analysis reveals a complex network among stromal cells, MCs and macrophages that contribute to the development of asthma and airway remodeling. Our findings provide a critical resource for understanding the principle underlying airway remodeling and inflammation in a monkey model of asthma, as well as valuable hints for the future treatment of asthma, especially the airway remodeling-characterized refractory asthma.